What Can I Do With a Patient With Diabetes and Critically Impaired Limb Perfusion Who Cannot Be Revascularized?. (December 2014) - Rümenapf, Gerhard; Morbach, Stephan
A patient with limb-threatening diabetic foot syndrome in whom relevant peripheral arterial occlusive disease is proven should receive arterial revascularization as soon as possible to avoid major amputation. However, 3 conditions may make it impossible to effectively restore limb perfusion: the patient will not profit from arterial revascularization owing to excessive tissue loss or sepsis ("too late"), the patient cannot be revascularized due to severe comorbidities ("too sick"), and arterial reconstruction is impossible because of technical and anatomical shortcomings in a patient who is otherwise fit for operation ("nonreconstructible limb perfusion"). This review outlines the therapeutic options specifically in the third group of patients in whom no technical option for surgical or endovascular revascularization exists.